Supplement to Common Knowledge

Proof of Proposition 2.4

Proposition 2.4.
If ω ∈ K*N(E) and EF, then ω ∈ K*N(F).

If EF, then as we observed earlier, Ki(E) ⊆ Ki(F), so

K1N(E) =  

Ki(E) =  

Ki(F) = K1N(F)

If we now set E′ = KnN(E) and F′ = KnN(F), then by the argument just given we have

Kn+1N(E) = K1N(E′) ⊆ K1N(F′) = Kn+1N(F)

so we have mth level mutual knowledge for every n ≥ 1.

Hence if ω ∈

KnN(E) then ω ∈

KnN(F). □

Return to Common Knowledge

Copyright © 2013 by
Peter Vanderschraaf <>
Giacomo Sillari <>

Open access to the SEP is made possible by a world-wide funding initiative.
Please Read How You Can Help Keep the Encyclopedia Free

The SEP would like to congratulate the National Endowment for the Humanities on its 50th anniversary and express our indebtedness for the five generous grants it awarded our project from 1997 to 2007. Readers who have benefited from the SEP are encouraged to examine the NEH’s anniversary page and, if inspired to do so, send a testimonial to